Porcine ovarian biometry, oocyte retrieval and quality of oocytes under different seasons in north east hill region - KUMAR, SURESH; DEVI, BHANITA; PURKAYASTHA, A; BHARTI, P K; DOLEY, S; KADIRVEL, G (The Indian Journal of Animal Sciences, 2016)
The present study was conducted to evaluate the effect of different seasons on porcine ovarian biometry and centred, oocyte retrieval and quality of oocytes in north east hill region of India. Porcine ovaries (1886) were collected over a period of 12 months from local abattoirs. The morphological studies revealed mulberry shaped multi- lobulated ovaries with an average weight of 4.435 ± 0.622 The average number of GF and CL were significantly higher in winter than monsoon) but not significantly different from pre-monsoon/summer. The number of CA was significantly higher in winter than monsoon and summer. The number of recovered oocyte from the visible follicles in oocyte collection medium had significantly higher number in winter than other two seasons. The oocyte percentage of grade-I, grade-II, grade-III and grade-IV were found to be 24, 36, 23 and 17%, respectively. The culturable oocytes were significantly higher during winter than summer and monsoon seasons. The season had significant effect on quality and quantity of porcine ovaries which could be well utilized in-vitro maturation and fertilization by the research in field of reproduction and biotechnology.